Bilingual Development in Children with Autism: Benefits and Supporting Strategies - Yohan Kurniawan; Wahyudi Rahmat; Ali Sorayyaei Azar (Universitas PGRI Sumatera Barat, 2024)
While bilingualism in children with autism spectrum disorder (ASD) is often perceived as challenging due to social and communication limitations, recent studies reveal substantial benefits for cognitive and social development through bilingual learning. This article examines factors impacting bilingual language acquisition in children with ASD, including family language environment, language input quality, and communication strategies. Using a literature review methodology, this study integrates findings from recent research on autism and bilingualism, focusing on effective approaches to support dual-language learning. Results indicate that strategic bilingual education positively affects communication, enhances cognitive flexibility, and improves social skills among children with autism. Practical strategies, such as structured language exposure, consistent usage, and visual supports, are discussed to aid educators and caregivers in fostering bilingual proficiency. These insights suggest that bilingual education, when implemented with appropriate techniques, serves as a valuable tool for enriching the overall developmental trajectory of children with ASD, reinforcing the need for inclusive and adaptable language programs.